Students' Metacognition in Solving HOTS Questions in the Context of the Flag Ceremony Yard Based on Initial Mathematical Abilities - Murtafiah, Wasilatul; Yunitasari, Anisa; Gembong, Sardulo; Alvarez, Joel I.; Yahya, Faridah Hanim (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2024)
This study aims to determine the ability of metacognition in solving HOTS problems in the context of problem related to activities in the context of the flag ceremony yard in solving problems based on initial mathematics ability. This research approach was descriptive qualitative involving 3 students as research subjects who were selected based on high, medium, and low initial mathematics abilities. The data were validated by using method triangulation techniques, namely tests and interviews. The results showed that students with high initial mathematics ability showed good metacognition skills in solving HOTS problems in planning, monitoring, and evaluating activities. However, they still need to improve their ability to evaluate the repair strategy if there is an error. Students with medium initial mathematical ability showed good metacognition skills in several aspects but needed to improve some aspects. Students with moderate mathematics ability have a good basic understanding of metacognition in planning activities. However, they need to improve their metacognition skills in monitoring and evaluating when solving HOTS problems. Meanwhile, students with low initial mathematical ability show limitations in utilizing metacognition skills in planning, monitoring, and evaluating activities, as a result, students experience difficulties in solving problems. So, teachers need to design teaching materials that can improve students' mathematical abilities and metacognition.